Efficient Determination of Mometasone by Derivatization Method Using UV-VIS Spectrophotometer: Efficient Determination of Mometasone by Derivatization Method Using UV-VIS Spectrophotometer - Abadi, Morteza Davood; Hariri, Roshanak; Souri, Effat; Barazandeh Tehrani, Maliheh (Iranian Journal of Pharmaceutical Sciences, 2023)
Mometasone furoate is a synthetic glucocorticoid with anti-inflammatory and anti-allergic effects, used for the treatment of allergic rhinitis, asthma, and dermatoses. In this study, a spectrophotometric method, as a selective and sensitive method, was developed for the determination of mometasone furoate after derivatization. For this purpose, mometasone was first reacted with sodium cyanide to prepare the drug derivatives. After that, the effects of different variables such as reaction solvent, concentration of the reagents, pH, and reaction time were studied. The final results showed that the determination method was linear in the range of 2-18 μg/ml. It seems that after 24 hours, the reaction was complete. The reaction product was characterized by NMR and FT-IR spectroscopy, and the accuracy and precision of the developed method were also studied. At last, the method was checked on Mometasone Ointment (0.1%), and the results were compared with the results of the HPLC method as a standard method.